Investigating English Learners’ Anxiety in Online English Learning at Higher Education: A Case Study of Moodle - Rizky Eka Prasetya (English Department - University of Sultan Ageng Tirtayasa, 2021)
The online environment created strenuous and barriers for language learners in higher education. It essentially has an impact on the learning progress and achievements individually. The study’s purposes are to explore and establish the online language learners’ anxiety in Learning Management System (LMS) Moodle. The Explanatory mixed methods of linear temporal order were employed to the 221 participants or respondents from four higher education and university in the South Jakarta area. The questioner was adopted from the Foreign Language Virtual Classroom Anxiety Scale as FLVCAS, and the semi-structured interview was adjusted to identify a better perspective with open-ended questions. Data analysis of this study revealed that learning classification of the contradictions of language learning online progress, including interaction anxiety, agitation of dismissive communicative assessment, the examination of anxiety, and the Anxiety of English for Foreign Language purposes-lesson material. Meanwhile, feature LMS Moodle’s specifical anxiety determined learning content, general interface, progress tracking feature, quiz, and assignment feature. Although, there are much integrating technology and language pedagogy and internet-correlated anxieties studies. Educational performance’s online characteristics became dominant to English learning, specifically LMS Moodle in higher education.